Best Answer

You would take the following steps for G = A / (1-R):

G = A / (1-R)

Multiply by (1-R):

G * (1-R) = A

Divide by G:

(1-R) = A/G

1-R = A/G

Subtract 1:

-R = (A/G) - 1

Divide By -1:

R = -((A/G) - 1)

Check Work:

Original Problem:

A = 12; R = 5

G = 12 / (1-5)

G = -3

Solving For R:

R = -((12/-3)-1)

R = 5

Therefore, R= -((A/G)-1)

User Avatar

Wiki User

βˆ™ 2012-05-31 05:29:54
This answer is:
User Avatar
Study guides


20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

See all cards
1200 Reviews

Add your answer:

Earn +20 pts
Q: How do you solve for r when G equals A divided by 1 minus r?
Write your answer...
Still have questions?
magnify glass
People also asked